2017
DOI: 10.1080/13546805.2017.1287693
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged temporal integration window in schizophrenia indicated by the double-flash illusion

Abstract: Our results are interpreted in favour of an enlarged temporal integration window for audio-visual stimuli in schizophrenia patients, which is consistent with previous research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Our findings have imported clinical implications regarding severe psychiatric conditions like autism and schizophrenia, where a widened TBW was demonstrated to occur (for example Stevenson et al, 2014c; Hass et al, 2017). Because even healthy subjects benefit from our training regarding speech intelligibility, one can assume that subjects with a chronically widened TBW would do so even more.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our findings have imported clinical implications regarding severe psychiatric conditions like autism and schizophrenia, where a widened TBW was demonstrated to occur (for example Stevenson et al, 2014c; Hass et al, 2017). Because even healthy subjects benefit from our training regarding speech intelligibility, one can assume that subjects with a chronically widened TBW would do so even more.…”
Section: Discussionmentioning
confidence: 56%
“…A widened TBW was demonstrated to occur in autism (Mongillo et al, 2008; Russo et al, 2010; Donohue et al, 2012; de Boer-Schellekens et al, 2013; Woynaroski et al, 2013; Zmigrod et al, 2013; Stevenson et al, 2014a,b,c), developmental dyslexia (Bastien-Toniazzo et al, 2010; for a critical discussion about the specific disease mechanism see Hairston et al, 2005; Francisco et al, 2017) and schizophrenia (De Gelder et al, 2003, 2005; Foucher et al, 2007; Ross et al, 2007b; De Jong et al, 2009; Pearl et al, 2009; Hass et al, 2017; Zvyagintsev et al, 2017). Zmigrod and Zmigrod (2016) showed additionally that a narrower TBW was associated with a better performance in verbal and non-verbal problem-solving tasks in a healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…In a healthy population, Ferri et al (2018) found increased susceptibility to the illusion in participants with high schizotypal scores, related to an increased TWI. Similarly, patients suffering from schizophrenia show an increased susceptibility to the illusion at longer SOAs, which is indicative of a lager TWI (Haß et al, 2016). However, no difference in the illusion perception appears at a short SOA, although changes in neural activity suggest aberrant multisensory processing in schizophrenia (Balz et al, 2016b).…”
Section: Clinical Applications and Future Directionsmentioning
confidence: 99%
“…The reason for the current opposing findings is not entirely clear, but they do align with findings in schizophrenia of increased proneness to other perceptual illusions that rely on multisensory integration. Specifically, individuals with schizophrenia are more prone than controls to perceiving the double-flash or fission illusion, in which one visual flash presented with two auditory beeps results in the perception of two visual flashes (Haß et al, 2017). Individuals with schizophrenia also experience the rubber hand illusion stronger and faster than controls (Peled, Ritsner, Hirschmann, Geva, & Modai, 2000).…”
Section: Discussionmentioning
confidence: 99%